Subaltern subjects and (necro)politics to combat COVID-19 in Brazil - Arruda, Dyego de Oliveira; Santos, Caroline Oliveira (Argumentum, 2022)
Starting from the concept of necropolitics, this article aims to problematize the way in which public policies to combat COVID-19 in Brazil, throughout 2020, influenced the context of death of subjects historically subalternized in the country. The specific focus of the analyzes was the strategies to encourage social distancing, in addition to emergency aid, considered essential public policies to face COVID-19. In summary, it was noticed that such public policies were implemented in Brazil from an arrangement that caused confusion, information asymmetry and agglomerations of historically subalternizes subjects. Therefore, it was concluded that public policies to combat COVID-19 ended up, in practice, transmuting themselves into necropolitics that amplified the risks of death of subalternized bodies in Brazil, in the context of the COVID-19 pandemic.